Overcoming profitability asymmetries in Power-to-X: Path2X method as a techno-economic solution - Antti Ylä-Kujala; Maija Luukka; Timo Kärri; Antero Tervonen (International Journal of Sustainable Energy)
Power-to-X (PtX) pathways are complex systems of multiple stakeholders with different business interests. PtX investments’ economic feasibility depends on stakeholders being profitable. Such stakeholder dynamics are ignored in current techno-economic analyses, although profitability asymmetries are a major obstacle for PtX investment approval. The aim of this study is to develop a generic analysis method – Path2X – to address asymmetric profitability within PtX pathways. Methodologically, the study adheres to design science research and uses case study for illustration. The Path2X method consists of a systematic lifecycle cost modelling and measurement approach. This comprises three cashflow components and a production flow to calculate a variety of techno-economic performance measures. Additionally, to evaluate stakeholder profitability, a multi-role approach combining role-level and pathway-level measures is suggested. The case study illustrates how a hydrogen provider faces a negative net cashflow, which ideally leads to profit sharing arrangements and a fairer distribution of profits among stakeholders.